Methodology for Integrated Design Optimization of Actuation Systems for Exoskeletons - Daniel Greve; Christian Kreischer (Robotics)
The engineering of actuation systems for active exoskeletons presents a significant challenge due to the stringent demands for mass reduction and compactness, coupled with complex specifications for actuator dynamics and stroke length. This challenge is met with a model-based methodology. Models for human body, exoskeleton and parametric actuation systems are derived and coupled. Beginning with an inverse dynamics human body simulation, loads in human joints are estimated, and the corresponding support torques are derived. Under the assumption of a control law ensuring these support torques, an optimization problem is stated to determine actuation system parameters such as the number of stator coils and number of battery cells. Lastly, results from the optimization are validated using sophisticated models. The methodology is applied to an exemplary exoskeleton and compared to an approach derived from previous studies.